Determinants of the time period from stroke onset to arrival at the emergency department: a GIS integrated hospital-based cross-sectional study - Shashank Kaggere Srinivasa; Madhu Basavegowda; Sulochanadevi B. Chakrashali; Suraj B. Manjunath; Mounika Sree Manivasagan (Scientific Reports)
Abstract Stroke is a serious public health problem in developing countries like India, leading to rising deaths and disability-adjusted life years related to stroke. Pre-hospital delay is a major concern in most acute stroke cases, affecting timely interventions and treatment outcomes. Hence the current study aimed to identify the factors influencing the time from stroke onset to arrival at the emergency department and to map the spatial distribution of stroke cases from the tertiary care hospital. We conducted a hospital-based cross-sectional study among stroke patients presenting to the emergency department of a tertiary care hospital in Mysuru. Data on sociodemographic, clinical, and pre-hospital factors, along with detailed addresses of the place of stroke onset, first and second consultation, and their proximal first referral units were collected. GIS mapping was done using the software ArcGIS v10.8.2, and statistical analysis was performed using SPSS v25. Most of the study participants were men, over 60 years of age, and residents from rural areas of Mysuru and its neighboring districts. The study found that only 25% of the stroke cases arrived within 4.5 h of symptom onset, with hemiparesis and slurred speech being the most common presenting complaints. Almost all the cases were within a 20 km radius of the first referral units with factors such as age group (p = 0.028), diabetes as a comorbid condition (p = 0.007), the decision taken for symptom onset (p < 0.01), the person involved in decision-making (p = 0.006), and the mode of arrival at the hospital (p = 0.004) being significantly associated with the duration from stroke onset to arrival at the hospital. This highlights the need for public awareness campaigns on stroke symptoms, the importance of early hospital presentation following stroke onset, and the capacity building of first referral units to provide timely emergency stroke care for people residing in rural areas.